The Conceptualisation And Operational Measurement Of Price Fairness Perception In Mass Service Context - Srikanjanarak, Saowanee; Omar, Azizah; T. Ramayah, T. Ramayah (Asian Academy of Management (AAM), 2009)
This paper aims to develop a measure of price fairness perception by extending price fairness conceptualisation to a multi-scale measure, thereby capturing its complexity in a mass service context. The service context is becoming increasingly competitive, particularly in the telecommunication industry, where a variety of service options is offered (e.g., mobile phone services). A review of price fairness perception literature usually focuses on the equity and social exchange theory and upon findings from exploratory research of the current market situation. In this article, the measure is conceptualised to entail a more extensive set of dimensions. These dimensions include the following: flexible price, reasonable price, acceptable price and superior price. Previous researchers have used actual price to focus on the structure and price comparison of competitors within the service industry. In contrast, this research has focused on the price comparison in terms of relative price. Additionally, we use a survey to elicit responses from 998 individual users of prepaid mobile phone services in Thailand. The results indicate a valid and reliable measure of price fairness perception, permitting us to understand how customers perceive that a price offered by service providers is fair. This understanding will help managers (and their respective organisations) to design an appropriate price strategy that fits what their customer's wants and needs while fostering a long-term relationship with them.